Withstanding Vulnerability throughout Adult Life Dynamics of Stressors, Resources, and Reserves - Spini, Dario; Widmer, Eric.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This open access interdisciplinary book integrates the major findings and theoretical advances of a 12-year research program run by the Swiss National Centre of Competence in Research LIVES research program hosted by the universities of Lausanne and Geneva, within a single comprehensive and coherent publication on vulnerability across adulthood. The book is based on the idea that vulnerability is an essential component of the life course that can inform how we use our resources, reserves and cope with stressors across the life course. It provides a unique interdisciplinary research framework based on the idea that vulnerability is a complex and dynamic process that can only be approached through a multidimensional, multilevel, and multidirectional perspective. This is an invaluable new resource for students and researchers in life course studies, and those from other disciplines willing to include life course factors in their research on vulnerability issues. Dario Spini is Professor of Social Psychology at the University of Lausanne and Director of NCCR LIVES. Eric D. Widmer is Professor of Sociology at the University of Geneva and co-director of NCCR LIVES.
INTRODUCTION: Inhabiting vulnerability throughout the life course,- Section 1: Vulnerability as a multidimensional process. Spillovers across life domains -- Subjective well-being, family dynamics and vulnerability -- Positive and negative spillover effects: Managing multiple goals in middle adulthood -- How personal relationships affect employment outcomes: On the role of social networks and family obligations -- When mobility meets gender in the multidimensional transnational life course -- Intimate partner loss in later life -- Synthesis: Multidimensional perspective of vulnerability and life course -- Section 2: Vulnerability at the articulation of levels -- Social policies, vulnerability and the life course: A complex nexus -- Vulnerabilities in local contexts -- How family and other close ties shape vulnerability processes -- The many faces of social connectedness and their impact on well-being -- Vulnerability and health issues: Trajectories, experiences and meanings -- Synthesis: Multilevel studies on vulnerability processes -- Section 3: The unfolding of vulnerable life trajectories -- Childhood socioeconomic disadvantage and health in the second half of life: The role of gender and welfare states in the life course of Europeans -- Ageing and reserves -- Vulnerabilities and psychological adjustment resources in career development -- On the sociohistorical construction of social and economic reserves across the life course and on their use in old age -- Life trajectories as products and determinants of social vulnerability -- Synthesis: Overcoming vulnerability? The constitution and activation of reserves throughout life trajectories -- Section 4: Combining methods to study vulnerability processes -- Life calendars for the collection of life course data -- Mixed method approaches for data collection in hard-to-reach populations -- Combining data collection modes in longitudinal studies -- Combining event history and sequence analysis to study vulnerability over the life course -- Joint longitudinal and survival models to study vulnerability processes -- Synthesis: Combining methods for the analysis of vulnerability processes across the life course -- Book conclusion -- CONCLUSION: Overcoming vulnerability in the life course: Reflections on a research program.
Keywords: Social medicine; Science -- Social aspects; Culture -- Study and teaching; Health, Medicine and Society; Medical Sociology; Science and Technology Studies; Cultural Theory